The prognostic impact of SYT‐SSX fusion type and histological grade in pediatric patients with synovial sarcoma treated according to the CWS (Cooperative Weichteilsarkom Studie) trials. Issue 1 (13th September 2016) - Stegmaier, Sabine; Leuschner, Ivo; Poremba, Christopher; Ladenstein, Ruth; Kazanowska, Bernarda; Ljungman, Gustaf; Scheer, Monika; Blank, Bernd; Bielack, Stefan; Klingebiel, Thomas; Koscielniak, Ewa
Abstract: Background: The aim of our analysis was the evaluation of the prognostic impact of SYT‐SSX fusion status and histological grading in synovial sarcoma (SS) of children and adolescents in the context of the consistent multimodal treatment strategy of the CWS (Cooperative Weichteilsarkom Studie; Cooperative Soft Tissue Sarcoma Study Group) and in comparison with other risk factors. Procedure: Between 1986 and 2006, out of 243 patients with SS, tumor samples from 84 patients with localized disease were available for RT‐PCR analysis. Outcome depending on fusion status in the context with known clinical risk factors was analyzed. Results: No prognostic significance was shown for SYT‐SSX fusion status and for histological grade. Highest significance of negative prognostic impact was found for large tumor size in uni‐ and multivariate analysis ( P < 0.01). Furthermore, male gender was shown to be an adverse prognostic factor in multivariate analysis ( P = 0.01). Conclusions: Based on our results, neither histological grading nor SYT‐SSX fusion status seems to be suitable for outcome prediction and risk stratification in localized SS treated according to the CWS. This is in contrast to several other publications concerning more heterogeneous age groups including children and adults, and this indicates that prognostic factors should not be interpreted apart from the particular study population and the therapeutic context.